2018
DOI: 10.1080/17445647.2018.1424656
|View full text |Cite
|
Sign up to set email alerts
|

Multi-temporal transect analysis of peri-urban developments in Faridabad, India

Abstract: Dynamic land-use changes in peri-urban areas in the Global South are often characterized by a juxtaposition of planned and unplanned, formal and informal, legal and illegal developments. India faces rapid (peri-)urbanization and great challenges to govern these sprawling, spatially fragmented, and socially uneven developments at the fringe of cities. Under these circumstances, up-to-date maps of (peri-)urban development processes are essential for effective governance. However, mapping the processes of urbaniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…These indicators can be modified and utilized for other study areas. As studies of other regions/cities have shown, a comparative approach might reveal additional insights [15,[69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…These indicators can be modified and utilized for other study areas. As studies of other regions/cities have shown, a comparative approach might reveal additional insights [15,[69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…occurs during the months of July to September is monsoon season). The city area experiences the features of the semi-arid climate with sandy soil, which contributes relatively low soil moisture 37 .
Figure 1 The extent of the study area (Map created with Arc Desktop 10.x Ver.).
…”
Section: Methodsmentioning
confidence: 99%
“…To solve the problem, a mix of non-residential services are needed to cover up 80% (standard), [10], of the total "weightsum map" (all services layers summed up together).…”
Section: Gis Analysis (Geo-processing Procedures)mentioning
confidence: 99%
“…Accordingly, the research will have to develop a spatiotemporal model framework that consists of a set of geo-spatial indicators and functions as a standardized measurement gauge to effectively and efficiently manage the growth and development of such areas [10].…”
Section: Introductionmentioning
confidence: 99%